Gender-specific Medicine and Work Life Balance in Female Physicians - Amano, Keiko (Japanese Journal of General Hospital Psychiatry, 2010)
Gender-specific medicine aims to advance research for diseases with different incidence or clinical causes between men and women, and to advance our physiological and biological knowledge which is limited to one gender, and finally to investigate the social status of men and women related to health. The ultimate aim is to reflect the results of such research in diagnosis, treatment, and prevention. Outpatient clinics for women based on EBM and NBM are one realization of the concept of gender-specific medicine. The first outpatient clinic for women in Japan was opened at Kagoshima University in May, 2001. Since then, the percentage of psychiatric symptoms as a chief complaint in outpatient clinics for women has increased to 20. How female physicians can enjoy a balanced, fulfilling life without compromising their professional careers is an important issue. For both males and females, their lives are becoming more consumed with a host of family and other personal responsibilities and interests. Therefore, it is increasingly important for all to recognize work-life balance. The Labor Standard Law guarantees expectant and nursing mother's leave before and after childbirth, limitation on overtime work or late-night work and child care time after childbirth. The Child Care and Family Care Leave Law secures the right for men and women to take child care leave or family care leave. Establishment of a system to assist male and female physicians to take family and child care leave on a daily basis is necessary.